2018
DOI: 10.4269/ajtmh.17-0966
|View full text |Cite
|
Sign up to set email alerts
|

Functional Studies of T Regulatory Lymphocytes in Human Schistosomiasis in Western Kenya

Abstract: Abstract.Immunoregulation is considered a common feature of Schistosoma mansoni infections, and elevated levels of T regulatory (Treg) lymphocytes have been reported during chronic human schistosomiasis. We now report that the removal of Treg (CD4+/CD25hi/CD127low lymphocytes) from peripheral blood mononuclear cells (PBMCs) of S. mansoni–infected individuals leads to increased levels of phytohemagglutinin (PHA)-stimulated interferon gamma (IFNγ) production and decreased interleukin-10 (IL-10) responses. Exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 53 publications
3
19
1
Order By: Relevance
“…20,21,51,52 Treg cells play a pivotal role in limiting hepatic immunopathological damage in schistosomiasis. 22,23,51 In this study, our results showed that ApoE deficiency caused higher levels of TC and TG in mice, which is consistent with the previous studies that ApoE-deficient mice have spontaneous elevations of total plasma cholesterol and triglycerides. 53 It is widely recognized that ApoE is a ligand for receptors that clear remnants of chylomicrons and very low density lipoproteins.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…20,21,51,52 Treg cells play a pivotal role in limiting hepatic immunopathological damage in schistosomiasis. 22,23,51 In this study, our results showed that ApoE deficiency caused higher levels of TC and TG in mice, which is consistent with the previous studies that ApoE-deficient mice have spontaneous elevations of total plasma cholesterol and triglycerides. 53 It is widely recognized that ApoE is a ligand for receptors that clear remnants of chylomicrons and very low density lipoproteins.…”
Section: Discussionsupporting
confidence: 93%
“…[47][48][49][50] Additionally, numerous studies have proved that the imbalance of Th17/Treg plays a pathogenic role during the development of schistosomiasis. [20][21][22][23]50,51 Our results showed that S japonicum infection up-regulated the frequencies of both hepatic Th17 and Treg in the ApoE −/− and WT mice.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Regulatory T cells expand during the chronic stage of S. mansoni murine infection and are present in S. mansoni infected patients ( 127 129 ). It has speculated that immunosuppression by Treg cell by the release of IL-10 and TGFβ may limit tissue pathology toward trapped eggs during infection ( 130 132 ).…”
Section: Mechanism Of “Eggs-cretion”mentioning
confidence: 99%